Pengaruh Kesadaran Wajib Pajak dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi pada KPP Pratama Probolinggo - Ginanjar Aji Satya Graha; Selfi Budi Helpiastuti; Joko Rizkie Widokarti (Universitas Dr. Soetomo Surabaya, 2024)
This research aims to analyze the influence of taxpayer awareness and tax knowledge on individual taxpayer compliance at the Probolinggo Tax Office. Increasing taxpayer compliance is needed to increase tax revenues. The problem is that the individual taxpayer compliance at the Probolinggo Tax Office during 2019 to 2021 has decreased. This compliance includes compliance with the submission of annual tax reports and tax payments. The grand theories used are attribution theory and compliance theory. This research uses an associative quantitative approach. The population of this research is made up of taxpayers at the Probolinggo Tax Office, with a total of 124.385. Sampling in this research used accidental sampling technique and obtained a sample of 277 respondents. The data collection technique used was distributing questionnaires. This research only examines two independent variable which are taxpayer awareness and tax knowledge, while the dependent variable is individual taxpayer compliance. Data analysis in this research used multiple linear regression analysis. The software used is SPSS version 26. Based on the results of the analysis for the variables of taxpayer awareness (X1), tax knowledge (X2), and individual taxpayer compliance (Y), the regression model is obtained as follows: Y = 5.546 + 0.212X1 + 0.564X2. The results of the coefficient of determination show that the two independent variables can explain the dependent variable by 61.4%. The results of the t test show that taxpayer awareness has an influence on individual taxpayer compliance and tax knowledge has an influence on individual taxpayer compliance.